Contempt of Court: A Comparison of U.S. Regulations and Their Implications for Legal Reform in Indonesia - Muhammad Salman; Rosa Tedjabuana (Golden Ratio of Law and Social Policy Review, 2026)
An independent judiciary is a fundamental requirement of a state that is governed by the rule of law. However, judicial independence may be undermined when court proceedings are disrupted, judicial orders are disregarded, or judges are subjected to intimidation through contempt of court. This study aims to compare the substantive and procedural regulations of contempt of court in the United States and Indonesia and formulate an adaptive model for legal reform in Indonesia. This study employs a normative juridical method using statutory, comparative, conceptual, and case-based approaches. The legal materials analyzed include 18 U.S.C. § 401, Federal Rule of Criminal Procedure 42, Law Number 1 of 2023 concerning the Criminal Code, and Law Number 20 of 2025 concerning the Criminal Procedure Code. The findings indicate that the United States regulates contempt of court through the doctrine of inherent judicial power, supported by substantive authority and procedural safeguards, including summary proceedings for direct contempt. Indonesia has made significant progress by codifying offenses against the administration of justice; however, it still lacks a specific procedural mechanism for addressing direct contempt swiftly and proportionately. This study argues that Indonesia should adopt an adaptive framework consisting of clear definitions, functional classifications, proportional sanctions, limited summary proceedings, and safeguards to ensure due processes and freedom of expression. This study contributes to ongoing legal reform efforts by proposing a balanced model that protects judicial authority while preventing the misuse of contempt powers.